A abordagem da consciência fonológica em livros didáticos do PNLD 2019-2022 adotados por escolas públicas do município de Fortaleza - Ceará para o Ciclo de Alfabetização - Lima, Yasmin dos Santos (2023)
This research aims to analyze how phonological awareness is presented in the activities of the Literacy Cycle’s didactic materials which involve the 1 st and 2 nd grades of elementary school initial grades. The choice of phonological awareness study has specific objectives, such as the reflection on methodological guidelines presented in the textbook regarding phonological awareness and the acquisition of reading and writing skills, the description of abilities concerning the development of phonological awareness present in the activities of the didactic materials incorporated in the Literacy Cycle by public schools in Fortaleza-CE and the qualitative analysis of skills based on the advancement of metaphonology displayed in textbooks on PNLD 2019-2022, adopted in the municipality. The wish to carry out this research arose after some personal and academic motivations, such as the study of theory in disciplines of adherence and participation in events, since we seek to deepen the theme, to show that phonological awareness being developed as a causal factor to expand the acquisition of reading and writing skills, to present the relevance of the theme, to contribute with basic education teachers and to emphasize the importance of the textbook as a useful methodological tool for studying. We substantiate on studies from Bryant e Bradley (1983), Gombert (1992), Adams et al (2006), Lemle (2007), Cagliari (2007), Soares (2018a, 2021b), Morais (2012a, 2020c), which build the discussion of metalinguistic awareness to phonological awareness, in order to relate to the Literacy concepts. Furthermore, we address the historical issues of the textbook and the Literacy methods with the contributions of the following theorists: Freitag (1993), Choppin (2004), Mortatti (2006), Pinton (2013), Albuquerque e Ferreira (2019), Mazzi e Amaral-Schio (2021). The corpus of investigation involves six didactic books of the Portuguese language, from Literacy Cycle, from PNLD 2019-2022, adopted in the municipality of Fortaleza, Ceará, three collections and each one embracing one book from 1 st grade and another from 2 nd grade. The methodology is a documentary and qualitative approach, considering the analysis of textbooks in methodological guidelines of didactic collections and selected exercises not only to the phonological component, but also its classification as to the aspect metaphonological. Through our results, we realize that the three collections reflect positively the methodological procedures regarding the CF aspect, both for learning to read and write and for enriching the educational practice. We selected 16 language skills based on the aspect of metaphonology taken from BNCC (2017) of exercises for a descriptive and qualitative analysis related to our specifics goals. The collections explore all the aspects, but some skills are developed in greater quantity and we highlight three groups of questions. First, group 01 has, the knowledge of speech sounds, with 351 questions. Second, we observed group 04, word segmentation, with 195 questions. Third, group 06 presents 137 questions and only, in didactic materials of 2 nd grade, relates the construction of the alphabetic system at the orthographic level. We emphasize the importance of contents that promote phonological reflection to stimulate the development of phonological awareness in the Literacy Cycle.